Pengaruh Pemberian Suplemen DHA pada Ibu Hamil terhadap Berat Badan dan Lingkar Kepala Bayi Baru Lahir - Dita Diana Parti (Fakultas Kedokteran Gigi Universitas Jember, 2015)
According to Howard Gardner, intelligent is potency biopsycosocial to process choosing information that can be using at one particular culture to overcome a problem or create nerve related to something new (brain). In womb, brain cell experiences of proliferation, migration, synaptogenesis and apoptosis. Enough nutrition is primary factor that play a part in growth body and brain. The purpose of the research is to verify difference body weight and circumference of baby head newborn baby between pregnancy mother that get and not get supplementation DHA by age pregnancy 20 week. Result shows that body weight at group control 3120.00±431 whereas at treatment group 3193.33±257 with value p=0.57. Circumference of baby head newborn at control group: 31.20±431 and treatment group: 33.07±997 with value p=0.743. Conclusion there is a asignificant difference between control group and treatment group in body weight but not in circumference of baby head.